2018
DOI: 10.1177/1362361318811153
|View full text |Cite
|
Sign up to set email alerts
|

Current profiles and early predictors of reading skills in school-age children with autism spectrum disorders: A longitudinal, retrospective population study

Abstract: This study explores current reading profiles and concurrent and early predictors of reading in children with autism spectrum disorder. Before the age of 3 years, the study cohort underwent a neurodevelopmental assessment following identification in a population-based autism screening. At age 8 years, reading, language and cognition were assessed. Approximately half of the sample ( n = 25) were ‘poor readers’ at age 8 years, meaning that they scored below the normal range on tests of single word reading and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The qualitative focus groups revealed why our parents regarded shared reading activities as opportunities to spend quality time with their child: they felt such activities to be revelatory, providing insight into their children's interests, passions and ways of thinking, as well as their language and literacy skills. Indeed, our questionnaire respondents indicated that their children tended to show stronger skills in, and preferences for, whole-word recognition (particularly with words of importance to the child) combined with weaker decoding and comprehensiona profile of reading skills that is characteristic of autistic children (Johnels et al, 2019;Lanter & Watson et al, 2012). It is noteworthy that our focus group participants almost never mentioned helping their autistic children to read unknown words.…”
Section: Discussionmentioning
confidence: 87%
“…The qualitative focus groups revealed why our parents regarded shared reading activities as opportunities to spend quality time with their child: they felt such activities to be revelatory, providing insight into their children's interests, passions and ways of thinking, as well as their language and literacy skills. Indeed, our questionnaire respondents indicated that their children tended to show stronger skills in, and preferences for, whole-word recognition (particularly with words of importance to the child) combined with weaker decoding and comprehensiona profile of reading skills that is characteristic of autistic children (Johnels et al, 2019;Lanter & Watson et al, 2012). It is noteworthy that our focus group participants almost never mentioned helping their autistic children to read unknown words.…”
Section: Discussionmentioning
confidence: 87%
“…Likewise, another explanation for our discordant results could be found in the composition of the sample, which might consist of students with ASD who have shown strengths in reading performance, both in decoding and comprehension. These profiles have been described in the literature as “skilled readers” ( Åsberg et al, 2019 ) or “average readers” ( McIntyre et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of academic performance, the variability in reading skills has led studies to identify reading profiles in samples of children and adolescents with ASD. In a longitudinal and retrospective study, Åsberg et al (2019) were able to determine three subgroups. A first subgroup, with “low reading performance,” which was the most frequent profile (approximately 50% of the participants), had below-average scores on both word reading and text comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, previous research has found that literacy is a significant area of need for children on the spectrum (Åsberg Johnels et al, 2019;Nation et al, 2006). Given literacy development begins long before children start school, this provides an opportune time to foster skills prior to the onset of challenges.…”
Section: Introductionmentioning
confidence: 93%
“…Autism is a neurodevelopmental condition, characterised by social communication challenges and specialised interests and/or routines (American Psychiatric Association, 2013) that occurs in approximately 1-2% of the population (Australian Bureau of Statistics, 2019;Maenner, Shaw, Baio, & Washington, 2020). Up to 65% of children on the autism spectrum 1 show impairments in reading, particularly reading comprehension (Åsberg Johnels, Carlsson, Norbury, Gillberg, & Miniscalco, 2019;Nation, Clarke, Wright, & Williams, 2006). Reading with understanding is crucial for participation in educational, community, and vocational domains, thus providing early literacy learning opportunities is of utmost importance for all children.…”
Section: Introductionmentioning
confidence: 99%